EMOTIVE INTERJECTIONS ON BATU BARA MALAY LANGUAGE - Akmal Akmal; Zulkarnain Sirait; Suparmadi Suparmadi (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: This study conducted to the semantics study especially in the emotive interjections. Interjections are to express the speaker’s states, feeling, actions, reactions, or attitude to a situation around the society. The objective of study is in Batu Bara Malay Language. This method research is qualitative research by using the observation to the field; interview some informants and digital (online) dictionary to get the data. The subjects are some Batu Bara Malay people. The researcher just interviewed the certain people who understood about the interjections. He took the data from tow different areas or districts which were in Batu Bara District, they are in Sei Balai District (Pematang Rambe Village) and Sei Bejangkar District (Talawi Village). From the inteview, he found only 6 (six) words of interjections which were in the society of Batu Bara Malay, namely; adoi, ahoi, huh, ih, idih, and aih. They expressed about the speaker’s emotive and cognitive in using the interjections (Witzbicka). The researcher also checked the data from the online dictionary of Malay language to make sure about the data. Keywords: Emotive, Interjections, Batu Bara Malay Language. Abstrak: Penelitian ini dilakukan untuk mengkaji semantik khususnya pada interjeksi emotif. Interjeksi digunakan untuk mengungkapkan keadaan, perasaan, tindakan, reaksi, atau sikap pembicara terhadap situasi di sekitar masyarakat. Tujuan penelitian ini adalah Bahasa Melayu Batu Bara. Metode penelitian ini adalah penelitian kualitatif dengan menggunakan observasi ke lapangan; wawancara dengan beberapa informan dan kamus digital (online) untuk mendapatkan data. Subjek penelitian ini adalah beberapa orang Melayu Batu Bara. Peneliti hanya mewawancarai orang-orang tertentu yang memahami tentang interjeksi. Ia mengambil data dari dua daerah atau distrik yang berbeda yang berada di Kabupaten Batu Bara, yaitu di Kecamatan Sei Balai (Desa Pematang Rambe) dan Kecamatan Sei Bejangkar (Desa Talawi). Dari hasil wawancara, ia hanya menemukan 6 (enam) kata interjeksi yang ada dalam masyarakat Melayu Batu Bara, yaitu; adoi, ahoi, huh, ih, idih, dan aih. Mereka mengungkapkan tentang emotif dan kognitif pembicara dalam menggunakan interjeksi (Witzbicka). Peneliti juga memeriksa data dari kamus daring bahasa Melayu untuk memastikan datanya. Kata kunci: Emosional, Kata Seru, Bahasa Melayu Batu Bara.